Perancangan Interior Bowling dan Billiard Club di Surabaya - Mariana Wibowo, Jacky Santosa (Intra, 2014)
Bowling and Billiard Club is a form of recreation that could accommodate the communitys needs, especially Surabaya. As the information spread and peoples interest to try something new rise, availability of functional Bowling and Billiard facility is needed. Hence, appears the idea to provide a recreational and sport facility which applies "Garden" theme concept design as a means of Family Entertainment. The design of this bowling and billiard club also including some types of support facilities such as Bowling Club Area, Billiard Area, VIP Room, Control Counter, a sports retail shop, gallery, cafÃ© area, lounge and bar area, as well as reading area.